The Creation of a Fourth-Century Witness to the Andreas Text Type: A Misreading in the Apocalypse's Textual History - Hernández, Juan (New Testament studies, 2014)
The publication of Josef Schmid's landmark work on the textual history of the Apocalypse seemingly established the Andreas Text Type as a fourth-century product. The primary evidence for Schmid's claim came from the fourth-century corrections of the Apocalypse in Codex Sinaiticus, corrections which bore a close resemblance to the Andreas text of the Apocalypse. Schmid's reconstruction, however, is flawed. The fourth-century corrections he identified are actually from the seventh century. The data supporting a fourth-century Andreas text type does not exist. Schmid's widely influential error appears to have been based on a misreading of Milne and Skeat's Scribes and Correctors of the Codex Sinaiticus.